Data workflows and visualization in support of surveillance practice - Gustafsson, Wiktor; Dórea, Fernanda C.; Widgren, Stefan; Frössling, Jenny; Vidal, Gema; Kim, Hyeyoung; Cha, Wonhee; Comin, Arianna; Rodriguez Ewerlöf, Ivana; Rosendal, Thomas (Frontiers in Veterinary Science, 2023)
The Swedish National Veterinary Institute (SVA) is working on implementing reusable and adaptable workflows for epidemiological analysis and dynamic report generation to improve disease surveillance. Important components of this work include: data access, development environment, computational resources and cloud-based management. The development environment relies on Git for code collaboration and version control and the R language for statistical computing and data visualization. The computational resources include both local and cloud-based systems, with automatic workflows managed in the cloud. The workflows are designed to be flexible and adaptable to changing data sources and stakeholder demands, with the ultimate goal to create a robust infrastructure for the delivery of actionable epidemiological information.